Demystifying the Specific Roles and Challenges of Educational Audiologists: A Narrative Review - Mohd Fadzil Nor Rashid; Tian Kar Quar; Nashrah Maamor; Foong Yen Chong; Mohd Normani Zakaria; Mazlina Che Mustafa; Hasrul Hosshan (Proceedings, 2022)
Educational audiology is a critical subspecialty in the field of audiology. An educational audiologist is responsible for providing services to hearing-impaired children in educational settings. Despite their responsibilities in performing their roles, they also encounter challenges. Therefore, the aim of this literature review was to demystify the specific roles of educational audiologists and challenges faced by them in real school environments. Materials and Methods: A search of the Scopus and Web of Science (WoS) databases was conducted in February 2020, and 17 relevant articles were identified. The inclusion criteria were educational audiology studies conducted in all countries or regions, and articles written in English. Results: The review identified six main themes concerning the roles of educational audiologists, and five main themes concerning the challenges that are faced by them. The findings from this review provide essential information on current educational practices in the audiology field. Conclusions: School-age hearing-impaired children have specific needs and require specific services to be provided to them by educational audiologists. In this review, the knowledge gaps in the roles and the challenges faced by educational audiologists are revealed accordingly. As a result, several recommendations are highlighted based on the review results. Notably, school-based audiological data for evidence-based practice in school settings are required and should be the focus of future research.